Recent advances in MXene-based sensors for Structural Health Monitoring applications: A review. (15th February 2022) - Grabowski, Krzysztof; Srivatsa, Shreyas; Vashisth, Aniruddh; Mishnaevsky, Leon; Uhl, Tadeusz
Abstract: Structural Health Monitoring (SHM) has a major role to play in the damage identification strategy of engineering structures. Sensors form an integral part of SHM and the development of sensors with minimum effect on measuring physical parameters leads to effective monitoring. The exciting discovery of MXene nanomaterials has made a tremendous impact on the field of sensors for various applications ranging from wearable health sensors to gas sensors. This review paper explores the sensing capabilities of MXene nanomaterials for SHM of engineering structures. MXenes are a family of two-dimensional nanomaterials with carbide or nitride layer (X layer) sandwiched between transition metal layers (M-layer); with more than 100 unique stoichiometric MXene combinations discovered to date, these nanomaterials can achieve wide tunability by varying ratios of M or X layers. Monolayer Titanium Carbide ( T i 3 C 2 ) MXenes are widely used for sensing applications and these MXenes have 330 ± 30 GPa modulus, 2.31 ± 0.57 μ Ω .m electrical resistivity, and 2.6 ± 0 . 7 cm 2 V − 1 s − 1 field-electron mobility. The review paper first covers the physical and chemical properties of MXene and MXene composites. Next, various MXene sensors developed in recent years are compared with conventional sensors; for example, T i 3 C 2 -MXene sensors have shown impressive response times as low as 7.13 ± 1 . 28 μ s which are comparable to piezoceramic sensors and outperform piezoresistive-type silicon sensors (for similar shocktube experiments). Additionally, recent advances in computational models for MXenes and their nanocomposites are provided to discuss further possibilities of virtual model development for the design of sensors. Sources of uncertainties of both physical sensors and computational models are discussed along with the effect of MXene material properties on measurement concepts like repeatability, reliability, and error estimation, etc., of the sensors. The purpose of reviewing both physical and computational models is to facilitate the use of MXene nanomaterial-based sensors in SHM applications.